Recyclable deep eutectic solvent catalyst and its application in continuous synthesis of PVB

CN122875288APending Publication Date: 2026-10-09EVERLIGHT YEAR POLYMER MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133147.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种可回收深共晶溶剂催化剂及其在PVB连续合成中的应用,解决了聚乙烯醇缩丁醛合成过程中传统无机酸催化剂污染重、现有深共晶溶剂受热易分解难回收,以及传统间歇式生产工艺传质效率低、产品品质不稳定的问题

Benefits of technology

1、本发明通过采用氯化胆碱与乳酸制备深共晶溶剂催化剂,替代传统无机酸,从源头消除了废酸排放问题,配合静置分层、添加焦亚硫酸钠以及减压蒸馏的回收工艺,有效抑制了深共晶溶剂在加热回收过程中的氧化分解,该工艺实现了催化剂的高效回收与多次循环闭环使用,在保持体系催化活性的同时,降低了催化剂的整体使用成本并减轻了后续的废水处理压力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875288A_ABST
    Figure CN122875288A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of polymer synthesis, and discloses a recyclable deep eutectic solvent catalyst and application of the deep eutectic solvent catalyst in continuous synthesis of PVB, wherein the catalyst is prepared from choline chloride and lactic acid according to a mass ratio of 1:1.5-1:2.0; and the application method comprises the following steps: continuously feeding polyvinyl alcohol solution, n-butyl aldehyde and the catalyst into a membrane dispersion micro-reactor to perform acetalization reaction; discharging the reaction product and standing for layering; separating the upper-layer suspension, washing with water and drying to obtain polyvinyl butylal acetal resin finished products; adding sodium pyrosulfite to the lower-layer mixed phase, and performing vacuum distillation to recycle the catalyst and send the catalyst back to a feeding unit for recycling. The deep eutectic solvent is used to replace traditional strong inorganic acid, the membrane dispersion micro-reaction continuous process is combined with the closed-loop recycling system, the problems of traditional process, such as waste acid, low mass transfer efficiency, are solved, and efficient recycling of the catalyst and continuous and efficient production of products are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer synthesis technology, specifically to a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB. Background Technology

[0002] Polyvinyl butyral possesses excellent flexibility, adhesion, light transmittance, and weather resistance, and is widely used in interlayer films for automotive safety glass, encapsulation films for photovoltaic glass, and adhesives. Currently, its industrial synthesis mainly involves the acetalization reaction of polyvinyl alcohol and n-butyral as raw materials under the action of a catalyst.

[0003] Traditional inorganic acid catalysts commonly used in existing technologies suffer from equipment corrosion problems, require neutralization after the reaction, and generate large amounts of acidic wastewater, resulting in high treatment costs. While ionic liquid catalysts exhibit good catalytic activity and are non-corrosive, they are expensive and have poor biodegradability, hindering large-scale industrial application. Deep eutectic solvents, as a novel green solvent, are increasingly being introduced into the synthesis process of polyvinyl butyral to replace traditional strong acids due to their low cost, low toxicity, and combined catalytic and dispersing effects. However, currently, deep eutectic solvents in these processes are mostly used only once, discharged directly with wastewater after the reaction, or rely on complex separation processes, leading to high actual operating costs. Furthermore, deep eutectic solvents exhibit poor thermal stability in heat recovery processes such as vacuum distillation; their internal hydrogen bond network is easily destroyed by heat, and they decompose easily under oxidizing atmospheres, causing a rapid decline in catalytic activity and making long-term recycling with high activity difficult.

[0004] In terms of production technology, existing polyvinyl butyral synthesis processes mostly employ traditional batch reaction processes. These batch reaction systems face physical limitations in the later stages of the reaction due to insufficient solid-liquid contact, resulting in low interphase mass transfer efficiency, long overall reaction time, and fluctuations in the degree of acetalization of the product, leading to poor product quality uniformity. Although novel equipment such as membrane dispersion microreactors have demonstrated advantages in other continuous chemical synthesis processes, such as uniform mixing and high mass transfer efficiency, there is currently a lack of continuous production solutions that match stably recyclable deep eutectic solvent catalysts with membrane dispersion microreactors. Therefore, developing a decomposition-resistant, highly recoverable deep eutectic solvent catalyst and combining it with continuous reaction equipment to achieve large-scale production of polyvinyl butyral is a problem that needs to be solved in this technological field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB. This solves the problems of heavy pollution from traditional inorganic acid catalysts, easy decomposition and difficulty in recovery of existing deep eutectic solvents upon heating, and low mass transfer efficiency and unstable product quality in traditional batch production processes during the synthesis of polyvinyl butyral.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Firstly, the present invention provides a recyclable deep eutectic solvent catalyst, employing the following technical solution: A recyclable deep eutectic solvent catalyst is provided, wherein the catalyst is prepared from a raw material comprising choline chloride and lactic acid, wherein the mass ratio of choline chloride to lactic acid is 1:1.5 to 1:2.0; the deep eutectic solvent catalyst is transparent and homogeneous, and the viscosity of the deep eutectic solvent catalyst is 50 to 80 mPa·s, and the pH value is 2.0 to 3.0.

[0007] By employing the above technical solution, choline chloride is used as the hydrogen bond acceptor and lactic acid as the hydrogen bond donor. When mixed in a specific mass ratio, they form a dense hydrogen bond network structure, lowering the system's melting point and making it a stable liquid at room temperature. The hydrogen ions dissociated from lactic acid provide the acidic environment required for the acetalization reaction; this acidity is milder than that of inorganic acids, reducing corrosion of metal equipment. Viscosity is controlled between 50 and 80 mPa·s to ensure catalyst flowability in pipelines and uniform mixing with other materials in the reactor; pH is controlled between 2.0 and 3.0 to provide a suitable proton concentration. Therefore, stable catalytic activity is achieved while reducing equipment corrosion and wastewater treatment burden.

[0008] Preferably, the catalyst has a freezing point of 8–12°C. By adopting the above technical solution, the deep eutectic solvent catalyst can be kept in a liquid phase state at normal room temperature and lower temperatures, preventing crystallization blockage during material transportation in industrial pipelines.

[0009] Preferably, the catalyst is prepared by the following steps: adding choline chloride and lactic acid in corresponding mass ratios to a reaction vessel, stirring at a temperature of 60–70°C and a stirring speed of 200–300 r / min for 40–50 min, and then allowing it to cool to room temperature. By employing the above technical solution, solid choline chloride dissolves in lactic acid and undergoes self-assembly at a specific temperature and stirring speed. This temperature range prevents thermal degradation of lactic acid and ensures that the resulting deep eutectic solvent catalyst exhibits a transparent and homogeneous state.

[0010] Secondly, this invention provides an application of a recyclable deep eutectic solvent catalyst in the continuous synthesis of PVB, employing the following technical solution: The application of a recyclable deep eutectic solvent catalyst in the continuous synthesis of PVB includes the following steps: Provide a polyvinyl alcohol solution and heat it for later use; prepare n-butyraldehyde and the deep eutectic solvent catalyst. The polyvinyl alcohol solution, n-butyraldehyde, and deep eutectic solvent catalyst are continuously fed into the membrane dispersion microreactor via metering pumps to achieve homogeneous acetalization reaction. The homogeneous acetalization reaction products are continuously discharged from the membrane dispersion microreactor and sent to a layering tank for static layering to obtain an upper layer of polyvinyl butyral suspension and a lower layer of deep eutectic solvent mixed phase. The upper polyvinyl butyral suspension is filtered, washed with water and dried to obtain the finished polyvinyl butyral resin product. The lower deep eutectic solvent mixture is fed into a vacuum distillation unit via a pipeline, sodium metabisulfite is added, and distillation is controlled to obtain a recovered deep eutectic solvent catalyst. The recovered deep eutectic solvent catalyst is then sent back to the feed end of the aforementioned metering feed pump for recycling.

[0011] By adopting the above technical solution, and through the combination of continuous microchannel reaction and antioxidant separation and recovery steps, production efficiency is improved while achieving the high-activity recycling of deep eutectic solvent catalysts. The specific reaction and recovery process is illustrated in the following steps: Step one is a continuous acetalization process. The membrane dispersion microreactor disperses n-butyraldehyde into tiny droplets and mixes them into the polyvinyl alcohol solution and the deep eutectic solvent catalyst, increasing the contact area between the liquid and liquid phases, reducing mass transfer resistance, and allowing the acetalization reaction to proceed continuously in a homogeneous state.

[0012] Step two is a static physical separation process. The generated product is insoluble in water and deep eutectic solvents and precipitates out in particulate form. After the material enters the separation tank and settles, it spontaneously separates into an upper suspension containing solid polymers and a lower mixed phase containing catalysts, utilizing the density and solubility difference between the product and the catalyst aqueous solution, thus achieving physical separation of the product and the catalyst.

[0013] Step three is the antioxidant distillation recovery process. During the heating of the lower mixed phase in vacuum distillation, the added sodium metabisulfite decomposes in water to produce bisulfite ions, which act as a reducing agent to consume dissolved oxygen in the system. At the same time, the bisulfite ions coordinate with the quaternary ammonium cation of choline chloride, stabilizing the hydrogen bond network of the deep eutectic solvent, inhibiting its oxidative decomposition in the thermal environment, and maintaining the catalyst structure and activity for subsequent closed-loop use.

[0014] Preferably, the concentration of the provided polyvinyl alcohol solution is 10% to 15%, and the heating temperature is 30 to 35°C; the molar ratio of n-butyraldehyde to polyvinyl alcohol in the polyvinyl alcohol solution is controlled between 0.9:1 and 1.0:1, and the amount of the deep eutectic solvent catalyst is 7% to 9% of the mass of polyvinyl alcohol in the polyvinyl alcohol solution.

[0015] By adopting the above technical solution, the concentration of polyvinyl alcohol solution is controlled to meet the hydrodynamic feeding requirements of the microreactor, the molar ratio of materials and the ratio of catalyst are controlled to achieve the acetal degree index of the target product, and side reactions caused by excessive catalyst are prevented.

[0016] Preferably, the membrane dispersion microreactor uses 316 stainless steel components and a polytetrafluoroethylene membrane with a pore size of 5-10 μm; the control parameters after the material is introduced into the membrane dispersion microreactor are: reaction temperature of 30-35℃, stirring speed of 300-400 r / min, and material residence time of 1-2 h.

[0017] By adopting the above technical solution, the acid resistance and specific pore size of the polytetrafluoroethylene membrane are used to achieve the size cutting and uniform dispersion of n-butyraldehyde. With the help of temperature, rotation speed and residence time parameters, the solid polymer is prevented from precipitating too quickly and encapsulating unreacted materials, thus ensuring that the materials complete deep acetalization.

[0018] Preferably, the conditions for the static stratification are: standing at 25-30°C for 30-60 minutes; the conditions for washing and drying the upper polyvinyl butyral suspension are: washing 2-3 times with water and drying at 80-90°C for 2-3 hours.

[0019] By employing the above technical solution, the settling parameters promote clear separation of the solid-liquid interface. The washing and drying steps remove trace amounts of catalyst and moisture adhering to the polymer particle surface, ensuring product purity.

[0020] Preferably, the amount of sodium metabisulfite added is 0.3% to 0.5% of the mass of the lower deep eutectic solvent mixed phase.

[0021] By adopting the above technical solution, an appropriate amount of reducing agent is provided to inhibit the oxidative decomposition of the catalyst, while avoiding excessive addition of inorganic salts that would lead to impurity accumulation in the subsequent recycling system.

[0022] Preferably, the distillation control parameters are: distillation temperature of 80-100℃, pressure of 0.08-0.1MPa, and distillation time of 1-1.5h.

[0023] By adopting the above technical solution, the boiling point of water is reduced under negative pressure conditions, the exposure time of deep eutectic solvent in high temperature environment is reduced, and thermal damage to its own hydrogen bond structure is prevented.

[0024] Preferably, the viscosity and pH value of the deep eutectic solvent catalyst are tested before each cycle. If the viscosity exceeds 50 mPa·s to 80 mPa·s or the pH value exceeds the range of 2 to 3, fresh deep eutectic solvent catalyst or lactic acid is added for adjustment.

[0025] By adopting the above technical solution, the changes in the physicochemical properties of the catalyst during multiple cycles can be monitored, lost or depleted components can be replenished in a timely manner, the acidity and flow properties of the catalyst can be maintained, and the stability of product quality in continuous production processes can be guaranteed.

[0026] This invention provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB. It offers the following advantages: 1. This invention uses choline chloride and lactic acid to prepare a deep eutectic solvent catalyst, replacing traditional inorganic acids and eliminating the problem of waste acid discharge at the source. Combined with the recovery process of static stratification, addition of sodium metabisulfite and vacuum distillation, the oxidative decomposition of deep eutectic solvent during heating recovery is effectively inhibited. This process realizes efficient recovery and multiple closed-loop use of the catalyst, reducing the overall cost of catalyst use and alleviating the pressure of subsequent wastewater treatment while maintaining the catalytic activity of the system.

[0027] 2. This invention utilizes a metering feed pump to continuously feed the reactants into a membrane dispersion microreactor for acetalization, changing the traditional batch reactor reaction mode. Through a continuous feeding and discharging mechanism, it breaks the conventional interphase mass transfer limitation, shortens the reaction residence time of the materials, and realizes continuous production. This technical solution improves production efficiency while reducing the equipment footprint, and the overall process conditions are mild, making it easy to modify and implement in existing industrial production lines.

[0028] 3. By limiting the specific pore size of the membrane dispersion microreactor and controlling the reaction temperature and stirring speed, this invention achieves rapid and uniform mixing and deep acetalization of polyvinyl alcohol aqueous solution and n-butyraldehyde. This control method avoids the problem of fluctuation in reaction conditions in traditional batch processes, ensuring the stability of the acetalization degree of the target product, polyvinyl butyraldehyde resin. Combined with subsequent water washing and drying steps, impurities and moisture are removed, resulting in a final product without obvious agglomeration and with uniform particle size distribution. Attached Figure Description

[0029] Figure 1 This is a schematic diagram showing the dual Y-axis correlation between the viscosity and freezing point of the deep eutectic solvent catalyst obtained in the preparation example of the present invention and the component distribution ratio. Figure 2 This is a schematic diagram showing the distribution of residual hydroxyl groups and acetalization degree in polyvinyl butyral resin prepared according to an embodiment of the present invention. Figure 3 This is a schematic diagram comparing the scatter distribution and mean trend of key indicators of quality stability of polyvinyl butyral resin products in the embodiments and comparative examples of the present invention. Figure 4 This is a schematic diagram illustrating the decay trend of the long-term cycling performance of the deep eutectic solvent catalyst as a function of the number of cycles in the embodiments and comparative examples of the present invention. Figure 5 This is a schematic diagram comparing the material utilization rate and environmental protection cost reduction operation accounting of the embodiments and comparative examples of the present invention; in Figure 4 It includes two subplots: subplot (a) is the catalyst mass recovery rate decay curve; subplot (b) is the catalytic activity retention rate decay curve. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a method for preparing a recyclable deep eutectic solvent catalyst, comprising the following steps: 100g of choline chloride and 150g of lactic acid were added to a reaction vessel and stirred at 200r / min for 50min at 60℃. After standing and cooling to room temperature, a transparent and homogeneous deep eutectic solvent catalyst was obtained. Its freezing point was 12℃, its viscosity was 50mPa·s, and its pH value was 2.0.

[0032] Preparation Example 2: This preparation example provides a method for preparing a recyclable deep eutectic solvent catalyst, comprising the following steps: 100g of choline chloride and 180g of lactic acid were added to a reaction vessel and stirred at 250r / min for 45min at 65℃. After standing and cooling to room temperature, a transparent and homogeneous deep eutectic solvent catalyst was obtained. Its freezing point was 10℃, its viscosity was 65mPa·s, and its pH value was 2.5.

[0033] Preparation Example 3: This preparation example provides a method for preparing a recyclable deep eutectic solvent catalyst, comprising the following steps: 100g of choline chloride and 200g of lactic acid were added to a reaction vessel and stirred at 300r / min for 40min at 70℃. After standing and cooling to room temperature, a transparent and homogeneous deep eutectic solvent catalyst was obtained. Its freezing point was 8℃, its viscosity was 80mPa·s, and its pH value was 3.0.

[0034] Examples 1-4: Example 1: This embodiment provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB, including the following steps: (1) Feed preparation: Prepare a 10% polyvinyl alcohol solution and heat the polyvinyl alcohol solution to 30°C for later use; prepare n-butyraldehyde and the deep eutectic solvent catalyst prepared in Preparation Example 1, with a molar ratio of n-butyraldehyde to polyvinyl alcohol of 0.9:1 and the amount of deep eutectic solvent catalyst is 7% of the mass of polyvinyl alcohol; (2) Continuous reaction: Polyvinyl alcohol solution, n-butyraldehyde, and deep eutectic solvent catalyst are continuously fed into the membrane dispersion microreactor through metering feed pumps. The membrane dispersion microreactor uses 316 stainless steel components and polytetrafluoroethylene membrane with a pore size of 5μm. The reaction temperature is controlled at 30℃, the stirring speed is 300r / min, and the material residence time is 2h to achieve homogeneous acetalization reaction. (3) Separation and purification: The reaction product is continuously discharged from the membrane dispersion microreactor and sent to the layer tank. It is allowed to stand at 25°C for 60 min. The upper polyvinyl butyral suspension is filtered, washed twice with water, and dried at 80°C for 3 h to obtain the polyvinyl butyral resin product. (4) Deep eutectic solvent recovery and recycling: The lower deep eutectic solvent mixture is fed into a vacuum distillation unit through a pipeline. Sodium metabisulfite is added at 0.3% of the mass of the deep eutectic solvent mixture. The distillation temperature is controlled at 80℃ and the pressure at 0.08MPa. The distillation is carried out for 1.5h to obtain the recovered deep eutectic solvent catalyst. The recovered deep eutectic solvent catalyst is sent back to the feed unit for recycling.

[0035] Example 2: This embodiment provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB, including the following steps: (1) Feed preparation: Prepare a 12% polyvinyl alcohol solution and heat the polyvinyl alcohol solution to 32°C for later use; prepare n-butyraldehyde and the deep eutectic solvent catalyst prepared in Preparation Example 2, with a molar ratio of n-butyraldehyde to polyvinyl alcohol of 0.95:1 and the amount of deep eutectic solvent catalyst is 8% of the mass of polyvinyl alcohol; (2) Continuous reaction: Polyvinyl alcohol solution, n-butyraldehyde, and deep eutectic solvent catalyst are continuously fed into the membrane dispersion microreactor through metering feed pumps. The membrane dispersion microreactor uses 316 stainless steel components and polytetrafluoroethylene membrane with a pore size of 8μm. The reaction temperature is controlled at 32℃, the stirring speed is 350r / min, and the material residence time is 1.5h to achieve homogeneous acetalization reaction. (3) Separation and purification: The reaction product is continuously discharged from the membrane dispersion microreactor and sent to the layer tank. It is allowed to stand at 28°C for 45 min. The upper polyvinyl butyral suspension is filtered, washed with water 3 times, and dried at 85°C for 2.5 h to obtain the polyvinyl butyral resin product. (4) Deep eutectic solvent recovery and recycling: The lower deep eutectic solvent mixture is fed into a vacuum distillation unit through a pipeline. Sodium metabisulfite is added at 0.4% of the mass of the deep eutectic solvent mixture. The distillation temperature is controlled at 90℃ and the pressure at 0.09MPa. The distillation is carried out for 1.2h to obtain the recovered deep eutectic solvent catalyst. The recovered deep eutectic solvent catalyst is sent back to the feed unit for recycling.

[0036] Example 3: This embodiment provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB, including the following steps: (1) Feed preparation: Prepare a 15% polyvinyl alcohol solution and heat the polyvinyl alcohol solution to 35°C for later use; prepare n-butyraldehyde and the deep eutectic solvent catalyst obtained in Preparation Example 3, with a molar ratio of n-butyraldehyde to polyvinyl alcohol of 1.0:1 and the amount of deep eutectic solvent catalyst is 9% of the mass of polyvinyl alcohol; (2) Continuous reaction: Polyvinyl alcohol solution, n-butyraldehyde, and deep eutectic solvent catalyst are continuously fed into the membrane dispersion microreactor through metering feed pumps. The membrane dispersion microreactor uses 316 stainless steel components and polytetrafluoroethylene membrane with a pore size of 10 μm. The reaction temperature is controlled at 35℃, the stirring speed is 400 r / min, and the material residence time is 1 h to achieve homogeneous acetalization reaction. (3) Separation and purification: The reaction product is continuously discharged from the membrane dispersion microreactor and sent to the layer tank. It is allowed to stand at 30°C for 30 min. The upper polyvinyl butyral suspension is filtered, washed with water 3 times, and dried at 90°C for 2 h to obtain the polyvinyl butyral resin product. (4) Deep eutectic solvent recovery and recycling: The lower deep eutectic solvent mixture is fed into a vacuum distillation unit through a pipeline. Sodium metabisulfite is added at 0.5% of the mass of the deep eutectic solvent mixture. The distillation temperature is controlled at 100℃ and the pressure at 0.1MPa. The distillation is carried out for 1 hour to obtain the recovered deep eutectic solvent catalyst. The recovered deep eutectic solvent catalyst is sent back to the feed unit for recycling.

[0037] Example 4: This embodiment provides a recyclable deep eutectic solvent catalyst and its application in the continuous synthesis of PVB, including the following steps: Using the method of Example 2, the recovered deep eutectic solvent catalyst was reused 8 times. Before each cycle, the viscosity and pH value of the deep eutectic solvent catalyst were tested. If the viscosity exceeded 50 mPa·s to 80 mPa·s or the pH value exceeded the range of 2 to 3, a small amount of fresh deep eutectic solvent catalyst or lactic acid was added for adjustment. Then, the synthesis of polyvinyl butyral and the recovery of deep eutectic solvent were carried out continuously according to the steps of Example 2.

[0038] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the catalyst is replaced with a 37% hydrochloric acid aqueous solution, the amount of hydrochloric acid aqueous solution is 7% of the mass of polyvinyl alcohol, the reaction equipment is replaced with a traditional batch reactor, the reaction time is extended to 4 hours, and the deep eutectic solvent recovery and recycling step is cancelled. All other aspects are the same.

[0039] Comparative Example 2: Compared with Example 2, the difference is that the deep eutectic solvent recovery and recycling step after separation and purification is cancelled, and the lower deep eutectic solvent mixed phase is directly discharged as wastewater. The deep eutectic solvent is used only once, and everything else is the same.

[0040] Comparative Example 3: Compared with Example 2, the difference is that sodium metabisulfite is not added before vacuum distillation in the deep eutectic solvent recovery and recycling step; all other steps are the same.

[0041] Comparative Example 4: Compared with Example 2, the difference is that in the raw materials for preparing the deep eutectic solvent catalyst, the mass ratio of choline chloride to lactic acid is replaced with 1:1.0, while the rest are the same.

[0042] Comparative Example 5: Compared with Example 2, the difference is that in the raw materials for preparing the deep eutectic solvent catalyst, the mass ratio of choline chloride to lactic acid is replaced with 1:2.5, while the rest are the same.

[0043] Test Examples 1-5: Test Example 1: Fresh deep eutectic solvents obtained from Preparation Examples 1 to 3 were used as test objects. They were placed in a constant temperature water bath and preheated to 25°C and kept at the temperature for 30 minutes to ensure that the thermal stress inside the sample was eliminated and that it was in a stable homogeneous liquid state.

[0044] A rotational viscometer was used with a coaxial cylindrical rotor and a set shear rate. The dynamic viscosity of each sample was measured under constant temperature of 25℃. Data was recorded after the instrument panel reading stabilized within the range of 0.5%. Each sample was tested three times in parallel with fresh material, and the average value was taken.

[0045] A precision pH meter was used. Before use, two-point calibration was performed using standard buffer solutions with pH values ​​of 4.00 and 6.86. During the test, the composite glass electrode was completely immersed in 15 mL of the deep eutectic solvent to be tested. A weak magnetic stirrer was turned on to assist ion diffusion. After standing until the millivolt potential reading no longer jumped, the true acidity value of the system was recorded.

[0046] The freezing point of the sample was determined by the step cooling curve method. A double-walled glass test tube containing 20 mL of deep eutectic solvent was placed in a programmed cooling bath and cooled at a rate of 1 °C / min. The temperature change of the system over time was collected in real time by a PT100 high-precision temperature sensor inserted below the liquid surface. The step cooling curve was plotted by a microcomputer, and the characteristic temperature inflection point on the curve that shows a clear exothermic plateau or a sudden change in cooling rate was determined as the freezing point.

[0047] Table 1. Test data of physicochemical properties of the deep eutectic solvent catalysts obtained in Examples 1 to 3 Figure 1 The horizontal axis represents the test object number, the left Y-axis corresponds to the broken line marked with a solid gray square in the figure, representing the dynamic viscosity value of the catalyst; the right Y-axis corresponds to the broken line marked with a hollow circle in the figure, representing the solidification point value of the catalyst.

[0048] Based on the data in Table 1, combined with Figure 1 The physicochemical properties of deep eutectic solvent systems play an important role in their mass transfer efficiency and catalytic activity in microreactors. Figure 1 The Y-axis on the left and the corresponding solid gray square broken line visually demonstrate the increasing viscosity with increasing lactic acid content, climbing from 51.2 mPa·s in Preparation Example 1 to 81.3 mPa·s in Preparation Example 3. This reflects that when lactic acid molecules, acting as hydrogen bond donors, dominate the space within the system, the intermolecular hydrogen bond cross-linking network becomes denser and more complex, leading to a sharp increase in the frictional resistance of sliding groups within the fluid. In contrast to the increase in viscosity, the Y-axis on the right and the hollow circle broken line record the freezing point decay trajectory, showing that the freezing point gradually decreased from 12.3℃ to 7.6℃. The melting point of pure choline chloride is typically as high as 302℃, while the melting point of pure lactic acid is around 18℃. The single-digit freezing point observed in this test confirms the strong supramolecular self-assembly behavior between the hydroxyl and carboxyl groups of lactic acid and the chloride ions of choline chloride.

[0049] This complex self-assembly effect breaks down the rigid lattice energy barrier of the original components, forcing them to maintain a highly homogeneous and stable liquid phase state under normal room temperature operating conditions. Previous fluid physics tests on micro-channel delivery revealed that once the viscosity of the catalyst system exceeds the critical value of 90 mPa·s, the material experiences significant flow resistance and a sudden increase in pressure drop across the membrane when passing through a 5 μm to 10 μm pore size polytetrafluoroethylene (PTFE) dispersion membrane. The viscosity distribution range of 51.2 mPa·s to 81.3 mPa·s shown in Table 1 for this batch falls precisely within the rheological operating window that ensures smooth cutting and uniform dispersion of the fluid within the microreactor. In conventional industrial production, there is often concern that the acidity of weak organic acids may not be sufficient to support macromolecular condensation. However, the actual acidity values ​​of 2.12 to 2.93 detected by the pH meter dispel this concern. This indicates that although the eutectic network binds most molecules, sufficient protons with adequate freeness remain within the system, providing ample active sites for the subsequent acetalization reaction between adjacent hydroxyl groups on the polyvinyl alcohol molecular chain and n-butyraldehyde. These basic physical property test results verify from a macroscopic physicochemical perspective that the designed catalytic system can fully meet the stringent hydrodynamic requirements of continuous delivery in microchannel pipelines, and also possesses the necessary thermodynamic basis for triggering and maintaining the target acetalization reaction.

[0050] Test Example 2: The first-synthesized polyvinyl butyral resin products obtained from Examples 1 to 3 after stratification, filtration, washing and drying were collected as test objects and placed in a vacuum drying oven at room temperature for 24 hours to completely eliminate the interference of adsorbed moisture on the surface and inside the pores.

[0051] Accurately weigh approximately 1.5g of resin sample and place it in a 250mL Erlenmeyer flask. Add 50mL of a mixed solvent containing an appropriate amount of pyridine and acetic anhydride titration solution. Heat the mixture to 95℃ to 100℃ in a constant temperature water bath equipped with a reflux condenser and maintain the temperature for 2 hours. The cross-linked polymer resin skeleton is completely dissolved and undergoes a full acylation reaction with the mixed solvent through high-temperature impregnation.

[0052] After the reaction is complete, remove the conical flask and place it on the lab bench to cool to room temperature. Add a small amount of distilled water to the flask to completely hydrolyze the excess acetic anhydride residue in the system. Then, slowly add a few drops of phenolphthalein indicator and shake well.

[0053] The above mixed solution was chemically titrated using a sodium hydroxide aqueous solution of known standard concentration. The color change of the droplet landing point was observed while the conical flask was continuously shaken. The titration endpoint was determined when the solution as a whole turned a faint pink color that did not fade for 30 seconds. The actual volume of sodium hydroxide standard solution consumed was recorded. A blank control experiment without resin was performed simultaneously. Finally, the mass fraction of residual hydroxyl groups on the polymer chain segment was calculated by converting the difference in the consumed volume, and the actual degree of acetalization was derived and calculated.

[0054] Table 2. Data on the conversion rate of polyvinyl butyral resins prepared in Examples 1 to 3 Figure 2 The horizontal axis corresponds to the test object numbers of Examples 1 to 3. The left Y-axis and the solid broken line marked with a solid gray diamond represent the residual hydroxyl content data obtained by titration calculation. The right Y-axis and the black dashed broken line marked with a hollow triangle represent the actual acetalization degree data obtained by final conversion.

[0055] Based on the data in Table 2, combined with Figure 2 The final degree of acetalization of polyvinyl butyral directly determines the flexibility and optical transparency of the resin product. Figure 2 The graph clearly shows two completely opposite trending lines. The gray solid diamond-shaped line representing the residual hydroxyl content reaches its lowest point of 18.06% in Example 2, while the black hollow triangle-shaped line representing the degree of acetalization rises to a peak of 78.15% at the same position. This close correspondence conforms to the stoichiometric transformation logic of the gradual replacement of hydroxyl groups on the polymer chain by n-butyraldehyde. The degree of acetalization in Examples 1 to 3 consistently exceeded 74%, verifying the feasibility of initiating and promoting the forward polycondensation reaction under weakly acidic conditions using a deep eutectic solvent system.

[0056] When using conventional low-speed stirred tanks for catalysis similar to weak organic acids, the polymer chains are prone to severe aggregation in the later stages of the reaction due to the phase transition from dissolution to precipitation. This prevents the unreacted hydroxyl groups within the polymer from fully contacting the free aldehyde groups, resulting in a conversion rate that often stagnates around 60% and cannot be improved. To overcome this bottleneck caused by limited interphase mass transfer, this method introduces the macromolecular reaction fluid into a membrane dispersion microreactor with micron-sized pores. As the fluid passes through the micropores, it is forcibly sheared into countless micro-sized droplets, allowing the polyvinyl alcohol molecules dissolved in the aqueous phase and the n-butyraldehyde in the organic phase to achieve an extremely amplified contact area at the liquid-liquid interface. Since the physical mass transfer area is fundamentally guaranteed, the subtle perturbations of the final conversion efficiency caused by different formulations and process parameters become apparent in the differentiated data of the examples. The reason why Example 2 exhibits the best degree of acetalization is mainly due to the fact that its 12% concentration polyvinyl alcohol solution and the 0.95:1 molar ratio achieved the optimal fluid viscosity and reaction kinetics equilibrium point in the reaction system.

[0057] In contrast, although Example 3 used a maximum solution concentration of 15% and excessively added n-butyraldehyde, the high polymer chain density and localized fluid retention caused by high viscosity inhibited the free diffusion rate of protons in the hydrogen bond network of the deep eutectic solvent, resulting in a rebound of the residual hydroxyl content detected by titration to 20.21%. Based on the above test results, it can be confirmed that coupling the supramolecular proton catalysis mechanism of the deep eutectic solvent with the polarization mass transfer effect within the microchannel not only enables the successful acetalization modification of the macromolecular framework without the corrosion damage of traditional strong acids, but also allows for precise parameter control to firmly lock the conversion efficiency of the target product within a high range that meets the requirements of industrial applications.

[0058] Test Example 3: Polyvinyl butyral resin prepared by the microreactor continuous process in Example 2 and polyvinyl butyral resin prepared by the conventional batch process in Comparative Example 1 were selected as comparative experimental objects. In order to examine the quality stability, three different batches of the above two processes were randomly sampled. All test samples were subjected to constant temperature and humidity pretreatment to eliminate environmental differences.

[0059] Each batch of resin samples was placed in a hot press and hot-pressed into a film with a thickness of about 1 mm at 150°C and 10 MPa pressure. After cooling and demolding, the film was cut into standard dumbbell-shaped test strips using a cutter.

[0060] The dumbbell-shaped specimen is clamped in the upper and lower clamps of the universal testing machine. The tensile rate is set to 50 mm / min. Axial tension is applied at room temperature until the specimen breaks. The instrument automatically records and outputs the tensile strength and elongation at break values ​​of the specimen. Each sample is tested in parallel five times to calculate the average result.

[0061] Weigh an appropriate amount of resin powder sample and add it to deionized water containing trace amounts of surfactant. Use an ultrasonic cell disruptor to process the sample for 10 minutes to obtain a uniformly dispersed suspension. Inject the suspension into the test cell of a laser particle size analyzer. Analyze the scattering pattern of the particles to the laser beam to obtain the volume average particle size of the resin particles and record the standard deviation of the particle size distribution output by the software.

[0062] Table 3. Test data of physical and mechanical properties and particle size distribution of different batches of products in Example 2 and Comparative Example 1 Figure 3The horizontal axis is divided into the microreactor process area of ​​Example 2 and the conventional batch process area of ​​Comparative Example 1. The left Y-axis corresponds to the tensile strength value, with the scatter points marked by squares. The solid black squares represent the batch data of Example 2, and the hollow squares represent the batch data of Comparative Example 1. The mean point of the two is connected by a solid black line. The right Y-axis corresponds to the standard deviation of particle size distribution, with the scatter points marked by circles. The solid gray circles represent the batch data of Example 2, and the hollow gray circles represent the batch data of Comparative Example 1. The mean point of the two is connected by a gray dashed line.

[0063] Based on the data in Table 3, combined with Figure 3 The content states that the degree of matching between the underlying fluid dynamics design of the reaction equipment and the catalytic system determines the final macroscopic physical properties of the polymer. Industrial sampling observations of routine batch reactors have revealed that when a strong inorganic acid with a mass fraction of 37% is added as a catalyst to a large-volume batch reactor, the acid concentration gradient is easily distorted due to dead zones in the stirring. This is precisely... Figure 3 The core reason for the wide scatter distribution of tensile strength in the three batches of Comparative Example 1, with the average value hovering only around 16.6 MPa, is that the macroscopic mixing in the traditional reactor cannot eliminate the interphase mass transfer resistance at the microscale. As the acetalization reaction progresses, the polymer precipitates in the aqueous phase due to the replacement of hydrophilic hydroxyl groups with hydrophobic butyral groups. The instantaneously precipitated resin particles undergo disordered cross-linking and bonding due to local overreaction, ultimately manifesting as a high standard deviation of particle size distribution on the right Y-axis, with values ​​ranging from 8.16 to 10.74.

[0064] This dramatic widening of particle size indicates that the particles contain numerous un-acetalized soft chain segments, severely disrupting the overall stress transfer network of the polymer skeleton. This makes the material highly susceptible to yielding and fracture at structural weak points under axial tension. When the processing technology was switched to the continuous system of the membrane-dispersed microreactor in Example 2, the solid black square scatter points on the left Y-axis not only rose to a high level above 23 MPa, but also showed extremely high convergence across the three batches of data. This is attributed to the forced shearing effect of the 8 μm PTFE membrane on the fluid, which shears the polyvinyl alcohol aqueous solution and the butyraldehyde organic phase dissolved in the deep eutectic solvent into a micro-droplet array with a large specific surface area. As the mass transfer distance is compressed to the micrometer level, the weakly acidic deep eutectic network can release proton catalytic sites synchronously and uniformly at the liquid-liquid interface, resulting in a homogeneous transformation of hydroxyl groups throughout the macromolecular chain.

[0065] Figure 3The extremely low standard deviation of the gray solid circular dots and gray dashed lines on the right, extending down to around 2.0, confirms that this microscopic homogeneous mixing effectively avoids localized sudden agglomeration and clumping. The highly uniform particle size indicates an extremely narrow molecular weight distribution and dense cross-linking within the resin. Under stress, the polymer chains can achieve uniform extension and load sharing, demonstrating the stable mechanical performance of Example 2 in Table 3, where the elongation at break consistently exceeds 210%. Through cross-validation across these dimensions, it is evident that simply adjusting the chemical formulation often fails to bridge the engineering gap in material performance stability. Only by embedding the catalytic properties of the eutectic system into continuous microchannel devices that provide extremely high interphase mixing entropy can the industrial pain point of batch fluctuations be truly eliminated and a substantial leap in product mechanical strength achieved.

[0066] Test Example 4: A long-term catalyst cycle test platform was constructed. The complete synthesis and recovery process of Example 4 was used as the test benchmark. Three alternative comparative experimental groups were set up simultaneously. The process parameters of Comparative Example 3, Comparative Example 4 and Comparative Example 5 were used to replace the corresponding steps in Example 4 to ensure that all test objects were operated in the same membrane dispersion microreactor equipment and vacuum distillation device.

[0067] The mass of the fresh deep eutectic solvent initially added to the system is precisely calibrated as the initial mass. After each round of vacuum dehydration distillation, the deep eutectic solvent at the bottom of the reactor is cooled to room temperature and discharged for weighing. The ratio of this weight to the initial mass is recorded as the mass recovery rate of that cycle. Subsequently, the recovered catalyst is directly pumped back to the feed unit to participate in the synthesis of polyvinyl butyral in the next round.

[0068] In the separation and purification stage of each round of synthesis reaction, the polyvinyl butyral resin powder that has been washed and dried is collected, and the actual degree of acetalization of the current batch of products is determined according to the acetic anhydride-pyridine titration method in Test Example 2.

[0069] The acetalization degree values ​​measured in each cycle were compared and divided with the absolute acetalization degree values ​​obtained from the first reaction of the test object using fresh deep eutectic solvent to obtain the catalytic activity retention rate. The complete synthesis and recovery closed-loop operation was performed 8 times in a row, and the performance degradation data after the 1st, 3rd, 5th and 8th cycles were recorded respectively.

[0070] Table 4. Test data on the continuous recycling performance of deep eutectic solvent catalysts under different process conditions. Figure 4The left subplot (a) records the trend of the physical mass recovery rate of the catalyst after multiple vacuum distillations, and the right subplot (b) maps the trend of the intrinsic catalytic activity retention rate corresponding to the recovered catalyst. Within both subplots, solid lines marked with solid black circles represent Example 4, dashed lines marked with hollow triangles represent Comparative Example 3, dotted lines marked with hollow squares represent Comparative Example 4, and dashed lines marked with hollow rhombuses represent Comparative Example 5.

[0071] Based on the data in Table 4, combined with Figure 4 The core economic value of deep eutectic solvent systems in industrial continuous production depends on their structural stability after undergoing multiple high-temperature dehydration and distillation processes. Figure 4 The mass recovery curve in the left subplot (a) reveals the effect of the hydrogen bond network ratio on the system's volatility resistance. Comparative Example 5 input a lactic acid ratio as high as 1:2.5 during the preparation stage. The corresponding hollow diamond-shaped dashed trajectory plummeted to 58.42% after 8 cycles. The physical mechanism of this mass loss is that the free lactic acid molecules, exceeding the electrostatic field of choline chloride and the hydrogen bond binding capacity, completely lost the barrier protection of the extremely low saturated vapor pressure of the eutectic in a 100°C reduced pressure environment, inevitably resulting in a large amount of water vapor escaping from the reaction system.

[0072] Figure 4 The hollow square dotted line at the bottom left of Comparative Example 4 illustrates another situation. Due to the donor ratio dropping to the 1:1.0 limit, the system viscosity abnormally increased. The stagnant fluid not only created stubborn physical residues on the microchannel walls, hindering recovery, but also, because of the initially low proton density within the cross-linked network, it suffered from a double disadvantage in the activity verification of the right-hand sub-figure (b): low starting point and rapid decay, ultimately resulting in an activity retention rate of only 61.42%. Overcoming the physical escape and wall-attachment barriers, the catalytic group disintegration phenomenon caused by purely chemical thermodynamics was clearly exposed in the data of Comparative Example 3. The recovery solution without added sodium metabisulfite showed obvious signs of yellowish-brown aging after several high-temperature baking processes. This color change is a macroscopic characterization of the self-esterification condensation and oxidative chain degradation of the hydroxyl and carboxyl groups within the lactic acid molecule under high-temperature aerobic conditions.

[0073] Figure 4The hollow triangle dotted line in the right-hand sub-figure, representing Example 3, demonstrates this degradation side reaction. The free proton source, which provides the catalytic site, is irreversibly depleted, causing the catalytic efficiency in the 8th cycle to be reduced to 51.27%. Addressing the multidimensional destructive pathways of physical volatilization and chemical oxidation, the 1:1.8 molar ratio in Example 4 is precisely controlled within the thermodynamically safe region of supramolecular assembly, completely embedding lactic acid molecules within a dense hydrogen-bonded three-dimensional framework, thus severing the volatilization pathway. Combined with 0.4% sodium metabisulfite pre-placed in the distillation vessel, this potent inorganic anti-decomposition agent preferentially quenches free oxidizing radicals in the system using the strong reducing properties of its low-valence sulfur element, forcibly breaking the thermal degradation chain of lactic acid. The stable, high-level trend of the solid black circular double line confirms the reliability of this intervention strategy. After eight complete cycles of chemical reaction and high-intensity thermal separation, the mass recovery rate of the deep eutectic solvent remained at 92.15%, and the activity retention rate, a core indicator of catalytic kinetics, never fell below the safe baseline of 95%. Based on the underlying modification of the formulation and antioxidants, this process system eliminates the structural collapse risk of organic protic acid catalysts in the long-term service environment.

[0074] Test Example 5: The lower liquid phase mixture discharged after the solid-liquid separation and purification operation in Example 2, Comparative Example 1 and Comparative Example 2 was collected as the test object. The sample of Example 2 included the distillate collected by condensation during the vacuum distillation stage and the circulating liquid left at the bottom of the vessel. The samples of Comparative Example 1 and Comparative Example 2 were the original waste liquid directly discharged into the collection pool.

[0075] The gas chromatograph equipped with a flame ionization detector was used to quantitatively test the above liquid phase samples. The instrument response factor was calibrated using a standard solution of n-butyraldehyde with a known mass concentration and a calibration curve was plotted. The mass of unreacted n-butyraldehyde in the liquid phase in a free or dissolved state was measured. The unconverted loss was compared with the initial total feed amount, and the comprehensive utilization rate of n-butyraldehyde in the actual production cycle was calculated and derived.

[0076] A quantitative liquid wastewater sample was drawn and placed in a digestion tube. A standard solution of potassium dichromate and a silver sulfate catalyst were added for high-temperature digestion. The amount of oxidant consumed was determined by titration to calculate the chemical oxygen demand (COD). The high-concentration organic wastewater pollution load data obtained from the test was applied to the current mainstream biochemical degradation process of industrial wastewater treatment plants, using the power consumption and reagent unit price model, to calculate the direct economic cost of wastewater treatment that must be allocated to each ton of polyvinyl butyral product produced.

[0077] The actual total consumption of catalysts and the single feed quota during the operation of each technical scheme were retrieved. Combined with the average spot trading prices of hydrochloric acid with a mass fraction of 37%, industrial-grade choline chloride and lactic acid in the current bulk chemical raw material market, the material flow data was scaled up proportionally to the standardized industrial capacity benchmark of 10,000 tons of resin per year, and the catalyst unit consumption procurement cost corresponding to each process route was determined in detail.

[0078] Table 5. Comparison of Comprehensive Economic and Environmental Core Indicator Calculation Data between Example 2 and the Comparative Example Figure 5 The horizontal axis represents the object number of each process route involved in the economic and environmental accounting. The left Y-axis corresponds to the broken line formed by the solid line and the solid black triangle marked with light gray filling, which is used to characterize the percentage of comprehensive utilization of n-butyraldehyde in the system after final accounting. The right Y-axis corresponds to the broken line formed by the dashed line and the hollow square mark, which reflects the converted comprehensive tonnage operating cost covering dimensions such as catalyst allocation and wastewater treatment.

[0079] Based on the data in Table 5, combined with Figure 5 In evaluating ton-scale processes for polymer polymerization reactions, a common problem is that increasing the conversion rate often requires forcibly injecting excessive amounts of expensive reactants into the system. Figure 5 The utilization rate curve on the left, formed by solid gray triangles, drops to a low of 83.17% at Comparative Example 1. This confirms that traditional batch reactor processes, due to poor mass transfer in the gas-liquid-solid three-phase system, have to rely on a large excess of n-butyraldehyde to maintain the forward reaction, resulting in a large amount of unreacted pure organic matter ultimately mixing into the waste acid and becoming unrecoverable. Comparative Example 2, by directly using a deep eutectic system to replace inorganic acid, saw a slight increase in utilization rate to 91.04%, but the hollow square dotted line on the right side of the graph shows that the overall operating cost per tonne rose to 1192.04 yuan / ton. The underlying logic for this cost overrun lies in the large amount of organic carbon chain skeletons abundant in the deep eutectic solvent. When these high-concentration organic components, originally used to build hydrogen bonds, are discharged into the wastewater treatment plant after separation, the chemical oxygen demand (COD) pollution level of the wastewater instantly exceeds the limit. The exorbitant wastewater treatment cost of 875.46 yuan / ton, coupled with the catalyst scrapping and remediation cost of 3.1658 million yuan, as shown in Table 5, renders this technical route economically unfeasible.

[0080] Based on data feedback from Example 2, the vacuum distillation module, built upon the physical properties of extremely low saturated vapor pressure, not only perfectly traps the eutectic system at the bottom of the vessel for indefinite circulation, but also vaporizes and extracts the n-butyraldehyde that was originally wasted in the aqueous phase along with the generated water. Quantitative traceability of the condensate by gas chromatography shows that this portion of vaporized n-butyraldehyde was captured without damage and pumped back to the front-end microreactor, enabling the comprehensive utilization rate of Example 2 to directly exceed engineering limits, reaching 98.63%. The circulation mechanism exhibits a strong cost-reduction effect; the catalyst purchase unit consumption in Table 5 is reduced to only 114,500 yuan. The closed material flow completely cuts off the channel for high-concentration organic matter to be discharged into external water bodies. The wastewater treatment plant only needs to treat a small amount of aqueous distillate containing extremely low residual organic matter, driving the wastewater treatment cost down drastically to 108.24 yuan / ton. The reduction in two core expenditures kept the total operating cost at a low level of RMB 119.69 per ton. The financial data of the entire chain from raw material extraction to end-of-pipe treatment directly verified that the invention, while eliminating the pain points of traditional chemical waste acid treatment, endowed the product with extremely high market premium space and environmental risk resistance.

Claims

1. A recyclable deep eutectic solvent catalyst, characterized in that, The catalyst is prepared from a raw material containing choline chloride and lactic acid, wherein the mass ratio of choline chloride to lactic acid is 1:1.5 to 1:2.

0. The deep eutectic solvent catalyst is transparent and homogeneous, with a viscosity of 50–80 mPa·s and a pH value of 2.0–3.

0.

2. The recyclable deep eutectic solvent catalyst according to claim 1, characterized in that, The catalyst has a freezing point of 8–12°C.

3. The recyclable deep eutectic solvent catalyst according to claim 1, characterized in that, The catalyst is prepared by the following steps: The choline chloride and lactic acid in the corresponding mass ratio are added to the reaction vessel and stirred at a temperature of 60-70°C and a stirring speed of 200-300 r / min for 40-50 min. The mixture is then allowed to stand and cool to room temperature.

4. The application of a recyclable deep eutectic solvent catalyst in the continuous synthesis of PVB, characterized in that, The application of the recyclable deep eutectic solvent catalyst according to any one of claims 1-3 includes the following steps: Provide a polyvinyl alcohol solution and heat it for later use; prepare n-butyraldehyde and the deep eutectic solvent catalyst. The polyvinyl alcohol solution, n-butyraldehyde, and deep eutectic solvent catalyst are continuously fed into the membrane dispersion microreactor via metering pumps to achieve homogeneous acetalization reaction. The homogeneous acetalization reaction products are continuously discharged from the membrane dispersion microreactor and sent to a layering tank for static layering to obtain an upper layer of polyvinyl butyral suspension and a lower layer of deep eutectic solvent mixed phase. The upper polyvinyl butyral suspension is filtered, washed with water and dried to obtain the finished polyvinyl butyral resin product. The lower deep eutectic solvent mixture is fed into a vacuum distillation unit via a pipeline, sodium metabisulfite is added, and distillation is controlled to obtain a recovered deep eutectic solvent catalyst. The recovered deep eutectic solvent catalyst is then sent back to the feed end of the aforementioned metering feed pump for recycling.

5. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, The concentration of the provided polyvinyl alcohol solution is 10% to 15%, and the heating temperature for standby is 30 to 35°C. The molar ratio of n-butyraldehyde to polyvinyl alcohol in the polyvinyl alcohol solution is controlled between 0.9:1 and 1.0:1, and the amount of deep eutectic solvent catalyst is 7% to 9% of the mass of polyvinyl alcohol in the polyvinyl alcohol solution.

6. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, The membrane dispersion microreactor uses 316 stainless steel components and a polytetrafluoroethylene membrane with a pore size of 5-10 μm. The control parameters after the membrane dispersion microreactor is introduced are: Control the reaction temperature at 30–35℃, the stirring speed at 300–400 r / min, and the material residence time at 1–2 h.

7. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, The conditions for standing are: standing at 25-30℃ for 30-60 minutes; The washing and drying conditions for the upper polyvinyl butyral suspension are as follows: Wash 2-3 times with water and dry at 80-90℃ for 2-3 hours.

8. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, The amount of sodium metabisulfite added is 0.3% to 0.5% of the mass of the lower deep eutectic solvent mixed phase.

9. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, The control parameters for the distillation are: Control the distillation temperature at 80–100℃ and the pressure at 0.08–0.1 MPa for 1–1.5 hours.

10. The application of the recyclable deep eutectic solvent catalyst according to claim 4 in the continuous synthesis of PVB, characterized in that, Before each cycle, the viscosity and pH of the deep eutectic solvent catalyst are tested. If the viscosity exceeds 50 mPa·s to 80 mPa·s or the pH exceeds the range of 2 to 3, fresh deep eutectic solvent catalyst or lactic acid is added for adjustment.